Tgfβ-neurotrophin interactions in heart, retina, and brain - Schlecht, Anja; Vallon, Mario; Wagner, Nicole; Erguen, Suleyman; Braunger, Barbara M. (Biomolecules, 2021)
Ischemic insults to the heart and brain, i.e., myocardial and cerebral infarction, respec-tively, are amongst the leading causes of death worldwide. While there are therapeutic options to allow reperfusion of ischemic myocardial and brain tissue by reopening obstructed vessels, mitigat-ing primary tissue damage, post-infarction inflammation and tissue remodeling can lead to secondary tissue damage. Similarly, ischemia in retinal tissue is the driving force in the progression of neovascular eye diseases such as diabetic retinopathy (DR) and age-related macular degeneration (AMD), which eventually lead to functional blindness, if left untreated. Intriguingly, the easily ob-servable retinal blood vessels can be used as a window to the heart and brain to allow judgement of microvascular damages in diseases such as diabetes or hypertension. The complex neuronal and endocrine interactions between heart, retina and brain have also been appreciated in myocardial infarction, ischemic stroke, and retinal diseases. To describe the intimate relationship between the individual tissues, we use the terms heart-brain and brain-retina axis in this review and focus on the role of transforming growth factor β (TGFβ) and neurotrophins in regulation of these axes under physiologic and pathologic conditions. Moreover, we particularly discuss their roles in inflammation and repair following ischemic/neovascular insults. As there is evidence that TGFβ signaling has the potential to regulate expression of neurotrophins, it is tempting to speculate, and is dis-cussed here, that cross-talk between TGFβ and neurotrophin signaling protects cells from harmful and/or damaging events in the heart, retina, and brain.
CRIS-Team Scopus Importer:2023-04-11
Keywords: Age-related macular degeneration; Brain-retina axis; Diabetic retinopathy; Heart-brain axis; Ischemic stroke; Myocardial infarc-tion; Neurotrophins; TGFβ signaling